Improving The Methodology Of Solving Chemistry Problems On The Basis Of Interdisciplinarity - Formanova Sh.B.; Idieva Nargiza Sadrievna (Genius Journals, 2024)
The issue of methods and methods of interdisciplinary implementation of problem solving in chemistry is considered to be one of the general problems of improving the methods of teaching chemistry. Interdisciplinary integration serves to master the content of academic subjects by implementing it in future chemistry teachers in Practical training of the science of chemical calculation in pedagogical universities. At the same time, it is necessary to more fully determine the didactic possibilities of interdisciplinary integration, to determine their functions in teaching, and thus to support future chemistry teachers to effectively use interdisciplinary integration in the teaching process
Keywords: Chemistry; teaching chemistry; teaching process